Analisis Konteks Situasional pada Podcast Warung Kopi Oleh Has Creative (Kajian Cyberpragmatics) - Amalia Rizki Salsabilah (BADAN PENERBIT STIEPARI PRESS, 2024)
Advancements in information and communication technology in the era of globalization have significantly transformed human interaction, including through social media and podcast platforms. This study focuses on the analysis of situational context in the